10 - REVELATIONS ON THE SICK COMPAGNION UNDER TREATMENT PROCESS AT A SCHOOL HOSPITAL (Fiep Bulletin - online, 2011)
The process accompanying under treatment causes changes in the personal, professional and social life of the sick and family. The companions at the hospital are required to stay and dedicate and integrate the team to attend the demands created by the treatment process. So, the companion acquires new experiences and relations which co figurate and identify his role in the hospital context. The goal is to present the revelations in the process of accompanying the sick by family members. It is a qualitative research developed in 2008 at the men's ward at the University Hospital in Londrina with 79 companions ofInterned patients. The data collecting was carried out by interviews conducted with objective and subjective questionnaires and the content analysis technique. The companions stayed at the hospital in average 20 days (73), full time (65) taking turns (45). They reveal the companionship while it occurs to favor expressions of affect, confidence and security of the patient as well as accompanying the treatment. Family members express difficulties like the overwork that causes anxiety physical and emotional fatigue. The revelations are directly related because the hospital is an unknown world which causes insecurity and difficulties handling the norms and rules from the treatment involving the patients ways of living.
Keywords: Living; Accompanying Process; Family